On Neutrosophic Filter of BL-algebras - Ibrahim Abdul; Karunya Helen Gunaseeli S (Ratio Mathematica, 2023)
The aim of this paper is to introduce the notion of neutrosophic filter in BL- algebras , and several key characteristics are investigated with illustrations. Additionally, we obtain few conditions of neutrosophic filter of BL-algebras